Hydrogel Eye Patch Combination of Tomato Extract and Astaxanthin as Anti-Aging - Dessy Erliani Mugita Sari; Ricka Islamiyati; Lilis Sugiarti; Revalina Nuri Ayushita; Zuni Novita Andriani (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Wrinkles are a signs of skin aging caused by intrinsic factors (dryness, thinning, wrinkles) and extrinsic factors like UV exposure, which increases Reactive Oxygen Species (ROS) and thereby triggering premature aging. Anti-aging efforts can be carried out through the use of cosmetic products, particularly topical agents containing antioxidants and cell regulators. This study aims to evaluate the physical and chemical characteristics, as well as the anti-aging effectiveness, of a combination of tomato extract and astaxanthin in the form of a hydrogel eye patch. The formulations were prepared in four variations, namely F0 as the base, F1 containing 1% tomato extract, F2 containing 1% astaxanthin, and F3 as a combination of both. Based on the test results, the best formula was F3, which contained a combination of tomato extract and astaxanthin. The evaluations conducted included organoleptic tests, weight and size uniformity, pH, swelling capacity, elasticity, and anti-aging effectiveness. The effectiveness test results showed that F3 provided the best result with a value of 61%. Statistical analysis using One-Way ANOVA showed a significance value of less than 0.05, indicating a significant difference between before and after the use of the hydrogel eye patch. Overall, the formulations F1, F2, and F3 met the applicable requirements and demonstrated that the combination of tomato extract and astaxanthin is effective for use in hydrogel eye patch formulations as an anti-aging agent, where as F0 did not meet the physical characteristics requirement, particularly in the pH evaluation, where the results exceeded the normal pH of human skin.